Without Prescription Anti Biotic Drugs Dispensed in Dhaka City: Antibiotic prescription without prescription - Sultana, Nusrat; Parvin, Roksana; Shamsuddoha, Nazla; Ahmad, Rahnuma; Jahan, Israt (Journal of the Medical College for Women & Hospital, 2024)
Background: Low income and high out-of- pocket drug costs both play an important role in medication restriction, consistent with basic economic principles. Such situation may lead to patient failing to complete the required treatment regimen or patients performing self -medication without consulting any physician, leading to, in case of antibiotic therapy , antimicrobial resistance. Therefore, it is important to monitor the dispensing of medication in pharmacies and to observe whether drugs are being sold without prescription. Aim: To survey the age group of patients, number of antibiotics sold without prescription by the local pharmacies and the cost borne by the patients in case of the antibiotic drugs used in Uttara, Dhaka. Materials and method: This cross-sectional survey was carried out between January 2017 to June 2017 in 3 big pharmacies in Uttara. In this study 10 selling time points were randomly selected to note the age groups of patients making antibiotic purchases without prescription at these pharmacies , quantity of antibiotics dispensed and the price paid by these buyers in the selected time points. Results: The number of antibiotics bought without prescription from each shop per time point ranged between 5 to 15. According to the age categories, the number range of antibiotics bought by patients in age group of 10-18 years and19-24 years was 10-15. Those patients in the age groups of 25-32 years and more than 55 years obtained 6 to 15 number of antibiotic drugs. The range of number of antibiotics attained by patients in the age groups of 33-42 years and 43-55 years was 5-15.These values were statistically significant (p<0.01). The average number of antibiotic drug obtained by patients in the 6 age groups ranged between 36 to 59 pieces and the findings were statistically significant (p <0.01) in all age groups. The average expenditure of antibiotic drug for the age groups ranged between Taka 841 (in more than 55 years age group) and Taka 1714 (in 10-18 years age group) and the outcome were statistically significant (p <0.01) in all age groups. Finally statistically significant (p <0.01) association was observed between the age groups of patients with the quantity and costing of the antibiotic bought by each age group. Conclusion: The findings of this study suggests that a large portion of the country’s population has access to drugs including antibiotics without the need for any prescription. A scenario as such may rapidly lead to antibiotic resistance. This study may help in promoting initiatives to control antibiotic usage without prescription and halt progress to antibiotic resistance. J Med Coll Women Hosp. 2024; 20 (1): 40-49